Tamarillo (Solanum betaceum Cav.): A Review of Physicochemical and Bioactive Properties and Potential Applications. Issue 7 (3rd October 2022) - Diep, Tung Thanh; Rush, Elaine C.; Yoo, Michelle Ji Yeon
ABSTRACT: Tamarillo ( Solanum betaceum Cav.) is a sub-tropical fruit with unique flavour and colour, known to be highly nutritious. Tamarillo has nutritional adequacy score of 7.4 (red type) to 7.9 (gold type) and it is a rich source of vitamins A, B6, C, dietary fibre and potassium. Phenolics, carotenoids and anthocyanins are considered as the main bioactive components, with 70 volatile compounds and organic acids that contribute to flavour. Potential health benefits include antioxidant, anti-obesity, anti-cancer and prebiotic properties. Anti-microbial and antifungal activities and proteolytic activity have also been demonstrated. This review summarizes chemical composition and bioactive properties of tamarillo from eight different countries (Argentina, Brazil, Colombia, Ecuador, New Zealand, Malaysia, Panama and Taiwan). Information on carbohydrates, dietary fibre, vitamins, minerals, volatiles, phenolic compounds, anthocyanins, total phenolic content and antioxidant activities of tamarillo are compared based on cultivars and geographical sources. Tamarillo possesses higher antioxidant activity than apples and kiwifruit. Applications of tamarillo as a functional ingredient for health, food, cosmetics and pharmaceutical products are also highlighted. Recently reported antimicrobial and antifungal properties make it even more attractive as a functional ingredient to enhance safety and shelf life of foods.